2020
DOI: 10.3390/w12102824
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Waterborne Pathogens in Surface and Drinking Waters. Are Water Treatment Plants (WTPs) Simultaneously Efficient in the Elimination of Enteric Viruses and Fecal Indicator Bacteria (FIB)?

Abstract: Monitoring the quality of water is a requisite to prevent outbreaks related to waterborne diseases, predominantly caused by pathogens like enteric viruses, usually transmitted via the fecal-oral route. This study aimed to survey a group of enteric viruses (Enterovirus, Norovirus genogroups I and II, and hepatitis A virus) in two surface water sources of drinking water, also intending to evaluate the extent of their elimination in the two water treatment plants (WTPs) involved in drinking water production. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Although a process control virus is highly recommended for the validation and interpretation of water monitoring processes [10,18,30], the low RNA recovery rates obtained for surface water in the present study recommend considering the addition of mengovirus only at the stages following the primary concentration step, where it will still be very useful, namely as control of RNA extraction (as initially proposed in the PCT/EP2007/055407 patent [17]). Furthermore, knowing that mengovirus induces cytopathic effects on Vero E6 cells (this study) and HeLa cells [24,28], its addition at the beginning of the process can make it difficult to interpret assays aiming the evaluation of the infectivity potential (for other virus) of the samples under survey, since the appearance of CPE may be exclusively due to the presence of mengovirus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a process control virus is highly recommended for the validation and interpretation of water monitoring processes [10,18,30], the low RNA recovery rates obtained for surface water in the present study recommend considering the addition of mengovirus only at the stages following the primary concentration step, where it will still be very useful, namely as control of RNA extraction (as initially proposed in the PCT/EP2007/055407 patent [17]). Furthermore, knowing that mengovirus induces cytopathic effects on Vero E6 cells (this study) and HeLa cells [24,28], its addition at the beginning of the process can make it difficult to interpret assays aiming the evaluation of the infectivity potential (for other virus) of the samples under survey, since the appearance of CPE may be exclusively due to the presence of mengovirus.…”
Section: Discussionmentioning
confidence: 99%
“…The significant differences between the recovery rates in the two water matrices, found in the present study (confirmed by the application of the Student's t-test), may be due to their very diverse characteristics. The surface water, having not undergone any treatment, contains a higher number of suspended particles and other agents that will be concentrated in the filter, while the drinking water was previously treated by processes that allowed the removal of suspended particles [10]. Consequently, the conditions for mengovirus adhesion to the filter will be different in the two situations, less efficient when surface water is collected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations